Treatment gaps in the implementation of LDL cholesterol control among high- and very high-risk patients in Europe between 2020 and 2021: the multinational observational SANTORINI studyResearch in context - Kausik K. Ray; Inaam Haq; Aikaterini Bilitou; Marius C. Manu; Annie Burden; Carlos Aguiar; Marcello Arca; Derek L. Connolly; Mats Eriksson; Jean Ferrières; Ulrich Laufs; Jose M. Mostaza; et al. (Elsevier, 2023)
Summary: Background: European data pre-2019 suggest statin monotherapy is the most common approach to lipid management for preventing cardiovascular (CV) events, resulting in only one-fifth of high- and very high-risk patients achieving the 2019 ESC/EAS recommended low-density lipoprotein cholesterol (LDL-C) goals. Whether the treatment landscape has evolved, or gaps persist remains of interest. Methods: Baseline data are presented from SANTORINI, an observational, prospective study that documents the use of lipid-lowering therapies (LLTs) in patients ≥18 years at high or very high CV risk between 2020 and 2021 across primary and secondary care settings in 14 European countries. Findings: Of 9602 enrolled patients, 9044 with complete data were included (mean age: 65.3 ± 10.9 years; 72.6% male). Physicians reported using 2019 ESC/EAS guidelines as a basis for CV risk classification in 52.0% (4706/9044) of patients (overall: high risk 29.2%; very high risk 70.8%). However, centrally re-assessed CV risk based on 2019 ESC/EAS guidelines suggested 6.5% (308/4706) and 91.0% (4284/4706) were high- and very high-risk patients, respectively. Overall, 21.8% of patients had no documented LLTs, 54.2% were receiving monotherapy and 24.0% combination LLT. Median (interquartile range [IQR]) LDL-C was 2.1 (1.6, 3.0) mmol/L (82 [60, 117] mg/dL), with 20.1% of patients achieving risk-based LDL-C goals as per the 2019 ESC/EAS guidelines. Interpretation: At the time of study enrolment, 80% of high- and very high-risk patients failed to achieve 2019 ESC/EAS guidelines LDL-C goals. Contributory factors may include CV risk underestimation and underutilization of combination therapies. Further efforts are needed to achieve current guideline-recommended LDL-C goals. Trial registration: ClinicalTrials.gov Identifier: NCT04271280. Funding: This study is funded by Daiichi Sankyo Europe GmbH, Munich, Germany.